Exploring the Influence of Quezon City Scholarships on Advancing Educational Equity and Fostering Social Mobility - Gracilla, Rowena L.; Arreglo, Rona-Jean R.; Bago, Nackelyn D.; Romero, Kristine Joy E.; Ulam, Jeffrey A.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study, "Exploring the Influence of Quezon City Scholarships on Advancing Educational Equity and Fostering Social Mobility," examines scholarship programs on advancing educational equity and promoting social mobility among Quezon City's underserved communities. Using a mixed-methods approach, it gathered insights from 174 scholarship recipients through surveys and interviews, focusing on how financial aid affects academic achievement, financial stability, and career opportunities. The findings indicate that these scholarships significantly enhance educational access by lowering financial obstacles and fostering long-term social mobility through improved career prospects and economic stability. Respondents expressed a high level of agreement on the program’s positive influence, with recommendations to cover non-tuition expenses and expand outreach for underserved groups. Ultimately, the research underscores the value of localized scholarship initiatives in fostering both individual development and broader community growth.